ARTIFICIAL INTELLIGENCE AND DIGITAL INNOVATION IN MATHEMATICS EDUCATION FOR CRITICAL THINKING: A SYSTEMATIC LITERATURE REVIEW - Prismadian Amalia Putri; Naning Sutriningsih; Suminto Suminto (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
This study presents a systematic literature review on artificial intelligence and digital innovation in mathematics education for critical thinking. The review aimed to identify research trends, forms of implementation, major findings, and research gaps in the literature. The study employed a Systematic Literature Review design guided by the PRISMA framework. Data were collected from the Scopus database. The initial search yielded several hundred records, which were filtered based on publication years 2020–2025, English language, open access status, subject area Mathematics, and source type Journal. After the filtering and screening process, 25 articles were selected for the final synthesis. The findings show that the literature on critical thinking in mathematics education is broader than the literature directly addressing artificial intelligence. Most studies focused on pedagogical approaches such as inquiry-based learning, realistic mathematics education, proof, problem solving, and computational thinking, while only a limited number of studies explicitly examined AI or generative AI in mathematics education. The review indicates that artificial intelligence and digital innovation have strong potential to support critical thinking through interactive learning environments, AI-assisted problem solving, and digitally mediated instruction. However, their contribution depends heavily on pedagogical design, teacher mediation, and the extent to which technology supports genuine mathematical reasoning. The review concludes that the integration of artificial intelligence in mathematics education remains an emerging field and requires stronger empirical evidence, clearer conceptualization, and more context-sensitive implementation to enhance critical thinking effectively.